Analisis Keuntungan Usaha Keripik Pisang Goroho Marindi Kelurahan Karombasan Utara Kecamatan Wanea Kota Manado - Worang, Nadila Jillf; Pangemanan, Lyndon Reindhart Jacob; Montolalu, Maya Hendrietta (AGRI-SOSIOEKONOMI, 2024)
The purpose of the study was to analyze the profit of goroho banana chips business “Marindi” in Karombasan Utara Village, Wanea District, Manado City. The research was conducted from February to March 2023. This research was conducted at the “Marindi” goroho banana chips business located in North Karombasan Village, Wanea District, Manado City. The data taken is primary data using direct interview techniques with business owners, based on questions (questionnaires) that have been prepared. The sampling method used in this research is a case study by determining the Goroho Banana Chips business in North Karombasan Village, Wanea District, Manado City. Data analysis carried out in this research is descriptive analysis method and presented in tabular form. Then measured using revenue analysis, profit, total costs incurred, and revenue cost (R/C). The results showed that the total revenue of the “Marindi” goroho banana chips business during January 2023 amounted to Rp13,140,000 / month with production costs / month of Rp6,062,765 overall the total profit earned by the “Marindi” business amounted to Rp7,077,235. The feasibility of the “Marindi” goroho banana chips business shows an R / C Ratio of 2.16 with an R / C value> 1, so the business profit is feasible to run.